PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH PADA INDUSTRI TAHU (Studi Kasus Pabrik Tahu WD Lamper Lor Semarang Selatan) - Rizani, Mohammad Debby; Ikhwanudin, Ikhwanudin; Iffah, Khilya Milkhatul; Prayogi, Gilar Maynalda (Universitas PGRI Semarang, 2023)
In the production process, the tofu industry produces solid and liquid waste. The waste contains organic matter with high levels of BOD, COD, and TSS and does not meet quality standards. If the waste is directly discharged into the environment, it will reduce the carrying capacity of the environment. This research was conducted at the WD Lamper Lor Tofu Factory, with the aim of planning the design and RAB for the construction of the wastewater treatment plant at the Tofu Factory. This research uses quantitative analysis methods which are presented in the form of numbers which are then explained and interpreted in the form of descriptions. The quality of BOD, COD, TSS, and pH were 144 mg/L, respectively; 380 mg/L; 98 mg/L; and 4.34. Based on the quality standards, the wastewater does not meet the requirements, so it is necessary to plan a wastewater treatment plant. Researchers plan the processing stages, namely Reservoir, Equalization, Anaerobic Digester, Gas Storage, Presettlement Tub, Anaerobic Biofilter, and Final Sedimentation Tub. The estimated effluent from the processing of BOD, COD, and TSS is 2,916 mg/L, respectively; 7.695 mg/L; 2.116 mg/L. In addition to processing it into water that is fit for reuse, the design of this wastewater treatment plant produces methane gas that can be used for the tofu-making process or can be used on a household scale. The total budget plan for the planning of the Wastewater Treatment Plant at the WD Tofu Factory is 31,106,117.05.